2016
DOI: 10.1128/cvi.00419-15
|View full text |Cite
|
Sign up to set email alerts
|

Human Memory CD4 + T Cell Immune Responses against Giardia lamblia

Abstract: ؉ EM T cells, as well as that of cells simultaneously producing both IL-17A and TNF-␣, to be significantly elevated in the Giardia-exposed individuals after 24 h of antigen stimulation. In supernatants of PBMCs stimulated with Giardia antigens for 6 days, we found inflammation-associated cytokines, including 1L-17A, as well as CD4 ؉ T cell activation and proliferation, to be significantly elevated in the Giardia-exposed individuals. We conclude that symptomatic Giardia infection in humans induces a CD4 ؉ EM T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 38 publications
(52 reference statements)
3
48
0
Order By: Relevance
“…The IL-17A mRNA level is elevated in the guts of cattle and mice infected with Giardia, and mice lacking IL-17A exhibit a severe defect in controlling infections with either Giardia muris or G. duodenalis (43)(44)(45). Moreover, IL-17A memory T cell responses correlated with more rapid elimination of infections in a cohort of travelers with giardiasis (46). Our data show that IL-17A responses are significantly reduced in the absence of signaling via C3aR.…”
Section: Discussionmentioning
confidence: 49%
“…The IL-17A mRNA level is elevated in the guts of cattle and mice infected with Giardia, and mice lacking IL-17A exhibit a severe defect in controlling infections with either Giardia muris or G. duodenalis (43)(44)(45). Moreover, IL-17A memory T cell responses correlated with more rapid elimination of infections in a cohort of travelers with giardiasis (46). Our data show that IL-17A responses are significantly reduced in the absence of signaling via C3aR.…”
Section: Discussionmentioning
confidence: 49%
“…Li et al [88] found a reduction in IL-17 responses in the absence of signaling via C3aR, which suggest that a decrease in mast cell recruitment also correlates with decreased IL-17 production. In human patients that have recovered from Giardia , IL-17 has been found to be upregulated when effector memory CD4 + T-cell are restimulated with Giardia antigen [89]; in addition, several studies [25, 87, 90, 91] reported the upregulation of IL-17 during murine or bovine infections, and delayed parasite clearance in IL-17 knockout mice has also been reported [87, 90]. Moving forward it will be interesting to understand the effector mechanisms triggered by IL-17 and the signaling mechanisms leading to activation of IL-17 production during giardiasis.…”
Section: Protective Immunity Towards Giardiamentioning
confidence: 99%
“…Giardia lamblia elicits both a cellular and humoral immune response, inducing cytokines such as tumour necrosis factor (TNF), interferon (IFN)‐y and interleukin (IL)‐17, as well as nitric oxide (NO), production of antigiardial IgA antibodies and intestinal mastocytosis . The relationship between giardiasis and allergy has been considered in the context of food allergy and allergic skin diseases .…”
Section: Protozoa and Allergy In Brazilmentioning
confidence: 99%